RNAWRE: a resource of writers, readers and erasers of RNA modifications. (1st July 2020) - Nie, Fulei; Feng, Pengmian; Song, Xiaoming; Wu, Meng; Tang, Qiang; Chen, Wei
Abstract: RNA modifications are involved in various kinds of cellular biological processes. Accumulated evidences have demonstrated that the functions of RNA modifications are determined by the effectors that can catalyze, recognize and remove RNA modifications. They are called 'writers', 'readers' and 'erasers'. The identification of RNA modification effectors will be helpful for understanding the regulatory mechanisms and biological functions of RNA modifications. In this work, we developed a database called RNAWRE that specially deposits RNA modification effectors. The current version of RNAWRE stored 2045 manually curated writers, readers and erasers for the six major kinds of RNA modifications, namely Cap, m 1 A, m 6 A, m 5 C, ψ and Poly A. The main modules of RNAWRE not only allow browsing and downloading the RNA modification effectors but also support the BLAST search of the potential RNA modification effectors in other species. We hope that RNAWRE will be helpful for the researches on RNA modifications. Database URL: http://rnawre.bio2db.com